The EWAS Classification of Scapholunate Tears: An Anatomical Arthroscopic Study - Messina, Jane C.; Van Overstraeten, Luc; Luchetti, Riccardo; Fairplay, Tracy; Mathoulin, Christophe L. (Journal of Wrist Surgery, 2013)
Treatment of scapho-lunate (SL) injuries is still a challenge for the surgeon, especially in chronic cases. The aim of the study isto experimentally cut, specific portions of scapholunate ligament and extrinsic ligaments and check their corresponding arthroscopic finding in order to understand the pathogenesis and develop a new classification system which is an evolution of the present arthroscopic classifications.Materials and Methods Thirteen cadaver wrists were studied under arthroscopy. Different portions of the scapho-lunate ligament were subsequently sectioned. In group A the sectioning sequence was: anterior SLIOL, RSC, LRL, SLIOL's proximal and posterior, DIC, DRC ligament and ST ligaments (8 cases). In group B it was: SLIOL's posterior and proximal, DIC, SLIOL's anterior, LRL, RSCL, DRC, ST ligaments (5 cases). The anatomo-pathological findings after each sectioning were correlated to the classification system proposed (Table 1).Results In group A, stage 3A was obtained when SL ligament's volar and intermediate portion and/ or SC/LRL ligaments were sectioned. A stage 3C was obtained when section of posterior SLIOL was sectioned as well. A stage IV when the DIC was also sectioned. In group B a stage 3B was obtained by cutting intermediate, posterior portion of the SLIOL ligament and DIC. A stage 3C was obtained when the anterior part of the SLIOL was also sectioned. In all cases, sectioning of the SLIOL lead to a stage 3C only if associated with sectioning of at least one of the extrinsic stabilizers (DIC or SC/LRL). Sectioning of DIC and SC ligament, in addition to SLIOL led to an arthroscopic stage IV. When ST, DRC and TH ligaments were also sectioned significant radiological signs appeared (stage V).Conclusions This study helps us to understand the anatomo-pathological scapho-lunate lesions in their different stages of partial lesions. Commonly called scapho-lunate lesions are complex, involving also extrinsic ligaments.